Secure state estimation and attack reconstruction for cyber-physical system with intermediate and robust observer - Xiaoyi Zheng; Zhen Zhu; Yan Lu (International Journal of Distributed Sensor Networks)
An intermediate and robust observer is presented in this article to robustly estimate secure state and reconstruct actuator attack for continuous-time/discrete-time cyber-physical system. First, we propose a general form of cyber-physical system under actuator attack and external disturbance, and then some assumptions are stated in order to facilitate further research. Second, a novel intermediate and robust observer is designed, based on which an augmented error equation is deduced, necessary and sufficient conditions for continuous-time/discrete-time cyber-physical system to obtain gain matrices are derived separately. Third, strict linear matrix inequality conditions are deduced by transforming the original problem into convex optimization problem. Finally, we conduct two simulation experiments with continuous-time and discrete-time unmanned ground vehicle model to show the effectiveness of the proposed secure state estimation and attack reconstruction approach.